2020
DOI: 10.1088/1742-6596/1695/1/012198
|View full text |Cite
|
Sign up to set email alerts
|

Study of spontaneous bioelectrical activity of two hierarchically connected neural networks in vitro

Abstract: Synchronization of neuronal subpopulations and spiking pattern propagation are essential features for bioelectrical activity of the brain. In this study, we proposed an engineering method to grow hierarchically connected networks in vitro through the microchannels and investigated the relations of local spiking propagation through the microchannels with integrated bursting events in the chambers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Previously, we showed that the microchannels, which consist of a sequence of triangular shapes, enable unidirectional axon growth between neurons [23]. Increasing the size of the last triangular segment also increased the efficiency of unidirectional axon guidance [30]. The Fish type consisted of three segments: two segments had a narrow triangular shape (200 µm length, 40 µm width), and one triangular segment was larger (200 µm length, 150 µm width) with rounded borders.…”
Section: Microfluidic Device Fabricationmentioning
confidence: 99%
“…Previously, we showed that the microchannels, which consist of a sequence of triangular shapes, enable unidirectional axon growth between neurons [23]. Increasing the size of the last triangular segment also increased the efficiency of unidirectional axon guidance [30]. The Fish type consisted of three segments: two segments had a narrow triangular shape (200 µm length, 40 µm width), and one triangular segment was larger (200 µm length, 150 µm width) with rounded borders.…”
Section: Microfluidic Device Fabricationmentioning
confidence: 99%
“…According to the predefined direction of axon growth, the modules were labeled Source and Target modules. We previously showed that the microchannels with asymmetric shapes provide unidirectional axon growth between neurons [ 50 ]. Here, we used the same type of microchannels that consisted of three segments: two segments had a narrow triangular shape (200 μm length, 40 μm width) and one segment had a large triangular shape (200 μm length, 150 μm width).…”
Section: Methodsmentioning
confidence: 99%